Management of behavioural change in patients presenting with a diagnosis of dementia: a video vignette study with Australian general practitioners - Jiwa, Moyez; Nichols, P.; Magin, P.; Pagey, G.; Meng, Xingqiong (Rosie); Parsons, Richard; Pillai, V. (B M J Group, 2014)
Objective: To test the impact of feedback on the proposed management of standardised patients presenting with behavioural change with a diagnosis of dementia in Australian primary care. Materials and methods: A video vignette study was performed with Australian general practitioners (GPs) in 2013. Participants viewed six pairs of matched videos depicting people presenting changed behaviour in the context of a dementia diagnosis in two phases. In both phases GPs indicated their diagnosis and management. After phase 1, GPs were offered feedback on management strategies for the patients depicted. Analyses focused on identification of change in management between the two phases of the study. Factors impacting on the intention to coordinate care for such patients were tested in a questionnaire based on the Theory of Planned Behaviour. Results: Forty-five GPs completed the study. There was significant improvement in the proposed management of three of the six scenarios after the intervention. Older GPs were more likely to refer appropriately (OR=1.11 (1.01 to 1.23), p=0.04.). Overall referral to support agencies was more likely after the intervention (OR=2.52 (1.53 to 4.14), p<0.001). Older GPs were less likely to intend to coordinate care for such patients (OR=0.89 (0.81 to 0.98) p=0.02). Participants who felt confident about their ability to coordinate care were more likely to do so (OR=3.79 (1.08 to 13.32) p=0.04).Conclusions: The intervention described in this study promoted multidisciplinary management of patients with behavioural problems with a diagnosis of dementia. Increasing practitioner confidence in their ability to coordinate care may increase the proportion of GPs who will respond to patients and carers in this context. Older GPs may benefit in particular.